Soft Computing Applications : Proceedings of the 6th International Workshop Soft Computing Applications (SOFA 2014), Volume 2 /: Proceedings of the 6th International Workshop Soft Computing Applications (SOFA 2014), Volume 2. (2016) - Unknown
No abstract available